THE PERCENTAGE OF TAX RECEIVABLES REVIEWED FROM TAX COLLECTION THROUGH WARNING LETTERS AND ENFORCEMENT LETTERS AT THE PRATAMA TAX SERVICE OFFICE OF SURABAYA RUNGKUT - Qadlizaka, Dendrit Yahya; Sulistyowati, Erna (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of Warning Letters and Enforcement Letters on the Percentage of Tax Receivables at KPP Pratama Surabaya Rungkut. The research method used is quantitative analysis and descriptive verification to examine the effect of each variable. The number of samples in this study was 35 data of warning letters, forced letters, and percentage of tax receivables from KPP Pratama Surabaya Rungkut. The type of data used in this study is secondary data. IBM Statistical Product and Service Solution (SPSS) software was employed to analyze the collected data. The gathered data was subsequently analyzed using classical assumption and multiple linear regression tests. The study results show that Tax collection through Warning Letters partially does not significantly impact the percentage of tax receivables. Tax collection through Enforcement Letters substantially affects the rate of tax receivables.